2021
DOI: 10.1259/bjr.20201316
|View full text |Cite
|
Sign up to set email alerts
|

Re-initiation of CT colonography services during the COVID-19 pandemic: Preliminary evaluation of safety

Abstract: Objective: The COVID-19 pandemic has led to cancellation and deferral of many cancer investigations, including CT colonography (CTC). In May 2020, BSGAR and SCoR issued guidelines outlining steps for conduct of CTC in the early recovery phase. We evaluated the implementation of these in four English hospital trusts. Methods: Ethical permission was not required for this multicentre service evaluation. We identified patients undergoing CTC over a 2-month period from May to July 2020 at four Trusts. We recorded d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…CTC is a faster procedure compared to colonoscopy and lends itself to social distancing, given that the process involves a computed tomography (CT) scan where no patient-staff physical contact is necessary. The study was done safely as no patients or staff involved in the CTCs were found to have COVID-19 after the test [37]. Additionally, CCE involves minimal physical contact between patients and staff; in fact, only one medical provider is needed to administer the test to a patient that can also be done remotely [38].…”
Section: Resuming Crc Screening During Covid-19 and Beyondmentioning
confidence: 99%
“…CTC is a faster procedure compared to colonoscopy and lends itself to social distancing, given that the process involves a computed tomography (CT) scan where no patient-staff physical contact is necessary. The study was done safely as no patients or staff involved in the CTCs were found to have COVID-19 after the test [37]. Additionally, CCE involves minimal physical contact between patients and staff; in fact, only one medical provider is needed to administer the test to a patient that can also be done remotely [38].…”
Section: Resuming Crc Screening During Covid-19 and Beyondmentioning
confidence: 99%